Evidence combination based on the degree of credibility and falsity - ONGYa-fei S; ANGXiao-dan W; EILei L; UEAi-jun X (Tongxin xuebao)
D-S evidence theory has been widely used in various fields of information fusion due to its efficiency in deal-ing with uncertain information.Unfortunately,combination of conflicting evidences by classical Dempster's rule may produce counter-intuitive results.To alleviate this problem,a new weighted average combination rule is proposed.Defi-nitions of correlation coefficient was first presented,followed by the introduction of falsity.Then the credibility of evi-dence is proposed.A new weighted coefficient is determined by credibility and falsity.To achieve convergence,the nor-malized weighted coefficient was suggested into the Dempster's combination rule to average the basic probability as-signment.Comparable numerical examples demonstrate that the proposed approach can combine conflicting evidences more effectively.Moreover,the proposed methodology can provide a faster identification of the observed object.